Plastics pollution: pathways, impacts, and regulatory challenges in marine environments - Bel Hassen, Malika; Bellaaj Zouari, Amel; Abdennadher, Moufida; Assaf, Jean-Claude; Nakad, Mantoura; Abboud, Rami; Khammeri, Yosra; Banni, Mohamed; Panzeri, Alberto; Gomes, Leonardo; Hamd, Wael (Frontiers in Environmental Science, 2025)
This review synthesizes existing literature on microplastics in marine ecosystems from various oceanic regions. Microplastics in marine environment originate from a range of sources, including land-based activities, rivers inputs and oceanic-based sources such as fishing, aquaculture, tourism and extreme oceanic events. Methodological and technical limitations, like sampling, identification and quantification, as well as data reporting and analysis, are key constraints in microplastics research, making it difficult to evaluate plastic debris volume in different marine environments. Microplastics have colonized diverse oceans, even polar areas. Their spatial distribution is influenced by their physicochemical properties as well as factors influencing their transport including wind driven waves, current and colonization by microorganisms. The most prevalent polymers in various oceanic systems are PE, PP, and PS, accounting for more than 60% of recovered microplastics. Microplastics affect both unicellular and multicellular marine organisms at various structural levels, causing significant disruptions that negatively impact their ecological and biological functions as well as their social behavior. This threatens both human and ecosystem health. Microplastics significantly impact marine ecosystem services, with total potential losses estimated to be between 1.18 and 2.16 trillion USD, accounting for about 2% of global GDP. Microplastics impair blue carbon ecosystems, reducing their carbon sequestration capacity and exacerbating the economic costs associated with climate regulation and coastal protection. The existing regulatory frameworks addressing plastic pollution are synthesized to identify gaps and highlight opportunities for enhancing and implementing more effective, evidence-based regulations that promote environmental sustainability.